2007
DOI: 10.1177/1073191107303217
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and the Five-Factor Model of Personality

Abstract: In this study of the discriminant, convergent, and incremental validity of the Almost Perfect Scale-Revised (APS-R), university students completed the APS-R, additional measures of perfectionism, the NEO Five-Factor Inventory-Form S, and measures of self-esteem and depression. The results revealed expected significant, but not completely overlapping, associations between the APS-R Discrepancy subscale scores and the Five-Factor Model of Personality (FFM) dimension of Neuroticism, and between the APS-R High Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
2
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 55 publications
13
133
2
12
Order By: Relevance
“…When measured with the MPS, other-oriented perfectionism showed a unique negative relationship with agreeableness corroborating previous findings that people high in other-oriented perfectionism show lower agreeableness (or higher social antagonism) than people low in other-oriented perfectionism, and that this is a unique characteristic of other-oriented perfectionism (e.g., Hill et al, 1997;Rice et al, 2007). When measured with the 1990 scale, other-oriented perfectionism showed a small negative correlation with agreeableness, but this relationship became nonsignificant in the multiple regressions when the overlap with the other forms of perfectionism was controlled for.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…When measured with the MPS, other-oriented perfectionism showed a unique negative relationship with agreeableness corroborating previous findings that people high in other-oriented perfectionism show lower agreeableness (or higher social antagonism) than people low in other-oriented perfectionism, and that this is a unique characteristic of other-oriented perfectionism (e.g., Hill et al, 1997;Rice et al, 2007). When measured with the 1990 scale, other-oriented perfectionism showed a small negative correlation with agreeableness, but this relationship became nonsignificant in the multiple regressions when the overlap with the other forms of perfectionism was controlled for.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, the present study found that other-oriented perfectionism showed no positive relationships with conscientiousness once the overlap with the other forms of perfectionism was controlled for. Therefore, other-oriented perfectionism should also not be considered part of "conscientious perfectionism" as Hill et al HOW OTHER-ORIENTED PERFECTIONISM DIFFERS 10 (2004) suggested based on the results of their factor analyses combining other-oriented perfectionism with aspects of perfectionism that are closely linked to conscientiousness such as self-oriented perfectionism and perfectionist personal standards Rice et al, 2007). Instead, other-oriented perfectionism appears to be an ambivalent form of perfectionism associated with high self-regard but low regard for others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, the finding is in line with previous findings indicating that perfectionistic strivings in sport are mostly adaptive when the overlap with perfectionistic concerns is controlled for (Gotwals, Stoeber, Dunn, & Stoll, 2012;Stoeber, 2011). Moreover, perfectionistic strivings are closely related to the personality trait of conscientiousness (Rice, Ashby, & Slaney, 2007). Consequently, the finding is also in line with previous findings indicating that conscientiousness is a protective factor against doping (Petróczi & Aidman, 2008).…”
Section: Perfectionism and Attitudes Towards Doping 10supporting
confidence: 82%